Ozone air pollution and ischaemic stroke occurrence: a case-crossover study in Nice, France. Issue 12 (5th December 2013) - Suissa, Laurent; Fortier, Mikael; Lachaud, Sylvain; Staccini, Pascal; Mahagne, Marie-Hélène
Abstract : Objectives: Relationship between low-level air pollution and stroke is conflicting. This study was conducted to document the relationship between outdoor air pollution and ischaemic stroke occurrence. Design: Time-stratified case-crossover analysis. Setting: University Hospital of Nice, France. Participants: All consecutive patients with ischaemic stroke living in Nice admitted in the University Hospital of Nice (France) between January 2007 and December 2011. Main outcome measure: Association (adjusted OR) between daily levels of outdoor pollutants (ozone (O3 ), nitrogen dioxide (NO2 ), particulate matter (PM10) and sulfur dioxide (SO2 )) and ischaemic stroke occurrence. Results: 1729 patients with ischaemic stroke (mean age: 76.1±14.0 years; men: 46.7%) were enrolled. No significant association was found between stroke occurrence and short-term effects of all pollutants tested. In stratified analysis, we observed significant associations only between recurrent (n=280) and large artery ischaemic stroke (n=578) onset and short-term effect of O3 exposure. For an increase of 10 µg/m 3 of O3 level, recurrent stroke risk (mean D-1, D-2 and D-3 lag) was increased by 12.1% (95% CI 1.5% to 23.9%) and large artery stroke risk (mean D-3 and D-4 lag) was increased by 8% (95% CI 2.0% to 16.6%). Linear dose–response relationship for both subgroups was found. Conclusions: Our results confirm the relationship between low-level O3 exposure and ischaemic stroke in high vascular risk subgroup with linear exposure–response relation, independently of other pollutants and meteorological parameters. The physiopathological processes underlying this association between ischaemic stroke and O3 exposure remain to be investigated.